Hooliganism : crime, culture, and power in St. Petersburg, 1900-1914 - Neuberger, Joan, 1953- (Studies on the history of society and culture, 1993)
In this pioneering analysis of diffuse underclass anger that simmers in many societies, Joan Neuberger takes us to the streets of St. Petersburg in 1900-1914 to show us how the phenomenon labeled hooliganism came to symbolize all that was wrong with the modern city: increasing hostility between classes, society's failure to "civilize" the poor, the desperation of the destitute, and the proliferation of violence in public spaces.--Publisher's description